The Application of Local Culture-Based Character Education at SMAN 4 Enrekang - Mustakim, Mustakim; Hasan, Hasan (Edumaspul: Jurnal Pendidikan, 2020)
Character is an important factor of future human progress. Character education has become a main issue in education, beyond being part of the learning process of shaping the morals of the children of the country, character education is now expected to be the principal foundation of Indonesia Gold 2025 ’s success. Various studies and facts show that the developed nation is a nation that has strong character. These character values are values that are extracted from cultural treasures that are in harmony with the characteristics of the local culture and not to "copy" other ward values that are not necessarily in accordance with the characteristics and personalities of the people and the local community. In general local culture is local ideas that are wise, full of wisdom, good value, which are embedded and followed by community members. Local wisdom is an alternative to the development of students’ character without leaving their regional identity. Local wisdom, which is the lifeline of social interaction in the region, will be more quickly absorbed by students to think, act and behave according to the guidance of local customs and culture. This research will be conducted at The State High School 4 Enrekang and aims to determine the application of local culture-based character education at SMAN 4 Enrekang and supporting and inhibiting factors of local culture-based character education and how the results of the application of local culture-based character education. This research is a qualitative descriptive study conducted at SMAN 4 Enrekang. Researchers will collect the data using observation, interviews, the questionnaire and documentation and analysis of data is qualitative analysis.